Sistem Pakar Diagnosa Penyakit Mata Menggunakan Metode Certainty Factor - Prasetia, Adam; Ardiansah, Temi (Journal of Information System Research (JOSH), 2024)
Diagnosing eye diseases is crucial for early identification of eye health problems, allowing for appropriate and effective treatment before the condition develops into a more serious one. Diagnose eye diseases to holistically understand the patient's eye condition, provide more specific treatment, and improve the patient's quality of life and well-being in the long term. This study aims to diagnose eye diseases using the certainty factor method so that the accuracy and efficiency of the eye disease diagnosis process. By utilizing certainty factors, this system aims to combine expert knowledge with symptom data inputted by users to provide a more precise and reliable diagnosis. Based on the results of the diagnosis of eye disease with rule 1 or Episcleritis disease with the final value of the certainty factor method of 22.63%, for rule 2 or Hordeolum disease with the final value of the certainty factor method of 23.45%, for rule 3 or Cataract disease with the final value of the certainty factor method of 26.79%, for rule 4 or Pterygium disease with the final value of the certainty factor method of 48.89%. Based on the final value of 4 disease rules, it was concluded that patient A was diagnosed with eye disease using the certainty factor method, namely Pterygium disease with a confidence level of 48.89%.